2015
DOI: 10.1111/ics.12202
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside protects against premature senescence induced by ultraviolet B irradiation in human dermal fibroblasts

Abstract: Our data provided the evidences for the protective role of salidroside against UVB-induced premature senescence in HDFs probably via its anti-oxidative property and inhibition on production of MMP-1 and pro-inflammatory cytokines, which indicated its potential utilization as an active ingredient in the preparation of photoprotective formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
2
23
0
3
Order By: Relevance
“…Fibroblasts. Our previous studies indicated that the optimal dose range of SAL for its protection against stress-induced premature senescence (SIPS) in human diploid 2BS fibroblasts is 5-20 μM [21,22]. In this study, we first observed the effects of SAL on replicative lifespan and biomarkers related to cellular senescence in human 2BS fibroblasts.…”
Section: Sal Delays Replicative Senescence Of Human 2bsmentioning
confidence: 91%
See 1 more Smart Citation
“…Fibroblasts. Our previous studies indicated that the optimal dose range of SAL for its protection against stress-induced premature senescence (SIPS) in human diploid 2BS fibroblasts is 5-20 μM [21,22]. In this study, we first observed the effects of SAL on replicative lifespan and biomarkers related to cellular senescence in human 2BS fibroblasts.…”
Section: Sal Delays Replicative Senescence Of Human 2bsmentioning
confidence: 91%
“…Our previous studies have indicated that SAL showed a potent antiaging effect in an accelerated mouse aging model induced by Dgalactose [20]. It also protects human fibroblast 2BS cells from premature senescence induced by H 2 O 2 or UVB exposure in human diploid fibroblasts [21,22], identified as stress-induced premature senescence (SIPS), which is mainly caused by oxidative stress and subsequent DNA damage. Besides, we found that SAL delays the replicative senescence of human diploid fibroblasts 2BS cells, which may be related to its stimulatory role on mitochondrial biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Salidroside is a phenylethanoid found in Rhodiola rosea L. , a plant that grows in high-altitude regions and has long been used as traditional medicine in China and Eastern Europe due to its beneficial effects against multiple pathological processes such as cerebral and endothelial dysfunction, hepatic injury and osteoporosis (Mao et al 2015). The anti-photoaging properties of this compound were investigated by Mao and colleagues (2015) using UVB-irradiated NHDF.…”
Section: Natural Compounds Used Against Photoagingmentioning
confidence: 99%
“…Salidroside treatment prevented UVB-induced cell cycle arrest and decreased the expression of the senescence-associated factors p21, p53 and p16. In addition, salidroside was able to protect the cells from UVB-induced synthesis of MMP-1 and of the pro-inflammatory cytokines IL-6 and TNF-α (Mao et al 2015). More recently, Xiao-Ying and colleagues (2016) showed that salidroside treatment is also able to protect HaCaT keratinocytes against UVB-mediated decrease in cell viability in a dose-dependent manner.…”
Section: Natural Compounds Used Against Photoagingmentioning
confidence: 99%
“…Salidroside has primarily been used as a brain tonic, a roborant or headache relief agent (8,12). Recently, salidroside has been studied in experimental animals for its protective effects against hypoxia, cold, radiation and heavy physical exercise (11).…”
Section: Introductionmentioning
confidence: 99%